The difference between male and female student's physical activity in urban region during school recess - Supriyanto, Agus; Kriswanto, Erwin Setyo; Prasetyo, Yudik; Andrianto, Sigit Dwi (Jurnal Keolahragaan, 2021)
Physical activity is one of the important components to support individual fitness and health. This study aims to determine differences in physical activity between male and female students of class V in urban areas during school breaks. This type of research is comparative descriptive. The research sample consisted of 54 elementary school students of grade V in urban areas in Depok Subdistrict, Sleman Regency, Yogyakarta Special Region. The technique used to determine the research sample is purposive sampling. The instrument in this study was the Nesco FJ 101 pedometer. The data analysis technique used in this study is a percentage. The results showed that the mean value of the male students 'physical activity level was 1897.5, while the female students' mean score was 1507. Based on the results obtained, there were differences between male and female students. It can be concluded that there is a significant difference between the physical activity levels of male and female grade V students during school breaks in the DIY urban area.